Penyelesaian Perjanjian Kredit Dalam Hal Debitur Telah Meninggal Dunia Tanpa Kepemilikan Asuransi (Studi di PT. Bank Nagari Cabang Utama) - Danovand, Calvin; Azheri, Busyra; Adelina Mannas, Yussy (Universitas Ekasakti, 2023)
Credit agreements are provisions that have legal certainty and apply as law to the parties to the agreement. In accordance with Article 1338 of the Civil Code paragraph (1) states that,